Ethics and the Dampening Effects of Pressure: The Moderating Role of Employment Level, Tenure, and Company Size (Journal of Organizational Psychology, 2022)
This study examines the relationship between a spectrum of employment-related variables (i.e., employment level, tenure, and company size) and Ethicality. A sample of 370 business employees of varying tenure and employment levels at companies of various sizes were surveyed to fill an important gap in the behavioral ethics literature. The survey included twenty-two questions, was both age (18 to 100 years) and genderbalanced, and well represented the United States of America. We have examined the role of a pressurized environment on employees in organizations to understand the extent to which they may be conducive or debilitating to ethical conduct. As hypothesized, we find a non-linear relationship between employment factors and Ethicality and a dampening effect of pressure across these key relationships.
Keywords: organizational psychology; ethics; business employees; pressure